Perceived Level of Knowledge and Acceptance of COVID-19 Vaccine Among Older Adults - Sibongga, Glorie; Degollado , Jerei Micah T; Escaran, Francis Alfred; Mina, Nytanya Yaffa T; Sison, Chelcon; Reantillo, Ejay M (Journal of Rural Community Nursing Practice, 2023)
The appearance of COVID-19 made a significant change on how people live their daily lives by putting the world in a state of a pandemic.  COVID-19 Pandemic affected the health of the people most especially the Older Adults who are more at risk of getting infected. This research aimed to discover the Perceived Level of Knowledge and Level of Acceptance of Older Adults about COVID-19 vaccines as inputs to quality improvement. A quantitative design was employed and a descriptive-correlational method was utilized to describe and correlate the relationship of demographic profile of the Older Adults and their perceived level of knowledge and level of acceptance regarding COVID-19 vaccination. This study determined that older adults are mostly in their 2nd  dose of vaccine and with booster dose, they belong in the age group of 60-65 years old, female, married and are high school and college graduates. A total of one hundred and fifty-seven of older Adults participated in the study. Descriptive statistics were used to analyze the demographic profile of the respondents while Eta coefficient and Eta squared were used to determine the relationship of demographic profile and the perceived level of knowledge and acceptance in view of the findings of the study. The results of the study suggest that the perceived level of knowledge and level of acceptance on COVID-19 vaccines were significantly correlated, r = .321, p < .05. This means that there is a positive weak correlation between perceived level of knowledge and level of acceptance. That is, the higher a person’s perceived level of knowledge about COVID-19 vaccines, the more likely they are to accept it. Appropriate health plan about convincing more older adults to get vaccinated with the COVID-19 vaccine particularly in the factors that address their common concerns. Also, to debunk myths that are known to many, and provide older adults with factual knowledge or information regarding the COVID-19 vaccines for them to accept in getting vaccinated.